Treatment of diabetic ketoacidosis in children and adolescents - Vanelli, M.; Chiarelli, F. (Acta Biomedica Atenei Parmensis, 2003)
Diabetic ketoacidosis (DKA) may be defined as a metabolic derangement characterized by hyperglycemia, acidosis and ketonuria. It is a crucial pediatric medical emergency. DKA may occur in children with diabetes at onset due to severe insulin deficiency, in established patients from failing to take insulin, acute stress, and poor sick-day management. The treatment of DKA has undergone a radical transformation over recent years. Among the major innovations the early adjustment of the hydroelectrolyte imbalance and the continuous I.V. infusion of microdoses of insulin are the most interesting. Despite appropriate use of insulin and fluids, and continuous clinical observation, the mortality rate has not improved, and has remained the same as that reported in the 1970s. DKA can be prevented by shortening the period of carbohydrate intolerance that usually precedes the diagnosis of Type 1 diabetes. Its prevention decreases morbidity and mortality and allows to save on the hospital costs. The aim of this paper is to review the main aspects of the treatment and prevention of DKA.